A HUMANIZAÇÃO NA ASSISTÊNCIA DE ENFERMAGEM EM UNIDADES DE URGÊNCIA E EMERGÊNCIA - Ribeiro de Almeida Rocha, Thatiane; de Oliveira Pinto, Fernanda (LINKSCIENCEPLACE, 2026)
We can say that humanize health means, value the relationship between the professional and the client based on respect and trust, giving a fair and better assistence to the client. The humanization ensures a pleasant service and a deeper contact with someone, aiming the someone's feeling, and not the object. The goal of this paper is to identify the perception of the nurse care on the humanization of the emergency and urgency rooms, and also knowing the process of humanize attendence in urgency and emergency rooms in the hospital emphasising the nursing care assistence. This studying is quantative, exploratory and interrelated, a semi structure questionnare with ten questions, of multiple choice was used for the data collection, with the objective of knowing what the nurse professionals think about the humanize assistence in the emergency and urgency cares. 18 professionals were part of the studying ( 11 nurses and 7 nurse technicians) the field of reaserch were 4 hospitals, two of them being public hispitals and two privte one in Campos dos Goytacazes/RJ. Before the techinical reading searched, and the results given by the reaserch it was possible to see that the professionals justify the non humanization assistence, due to the lack of resources, in a overwork place, which leads to a difficult update about the humanization assistence, besides not having financial support for it.